A cross sectional study on depression, anxiety and stress among the first-year medical students - Gupta, Shailesh; Potdar, Pratishtha; Singh, Ranjana; Shukla, Kamlesh Kumar (International Journal Of Community Medicine And Public Health, 2022)
Background: A study based on depression, anxiety and stress score (DASS) among youngsters is crucial to know about their levels towards dispersion, anxiety and stress. It is significant to conduct such study due to fast life and behaviour changes among society especially in metro city. To know the levels of DASS among first year medical students, and to compare their DASS score levels between male and female students. Methods: A total of 146 first year medical students were included for completion of the study. Pre-designed scale (DASS scale 21) was used to collect the data. This study was conducted at the department of community medicine, Noida international institute of medical science, Guatam Budh Nagar near Delhi, India. Univariate and bivariate tables along with chi-square test have been used for presentation of data. Independent t test has also been employed to compare between DASS mean score among male and female respondents. Results: Mean±SD scores of depressions, anxiety and stress of students were found 10.23±8.63, 10.35±8.66 and 11.50±8.29 respectively according to DASS scale. Majority of the students were reported about stress due to new destination, relation with friends and vast syllabus. Conclusions: It was statistically insignificant difference for mean score of depression, anxiety and stress respectively between male and female students. It was also insignificant difference between age groups (<20 and ≥20 years) and their DASS levels. Anxiety and Stress score were observed more for female in comparison to male students.